Amelioration de la gestion des sols par lintroduction de legumineuses dans les systemes cerealiers des savannes africaines - Carsky, R.J.; Douthwaite, Boru; Manyong, Victor M.; Sanginga, N.; Schulz, S.; Vanlauwe, Bernard; Diels, J.; Keatinge, J.D.H. (2003)
Lessons for appropriate soil management technology generation for the savannas and their application to the grain legume-cereal rotation system There are many legume-based techno logies capable of regenerating soi l ferti lity but few are being adopted by fa rmers in West Africa . At the Tn ternationa l Institute of Tro pica l Agriculture (TTTA) we found that alley cropping and cover cropping systems are biologica ll y sustainable but have low adoption by farmers in the medium term. Negacive reactions by farmers stimulated us to consider grain legume rotations for soi.J fertility maintenance, a decisio n that permined a concentra tion of efforts by several disciplines on the same system. The imrnediate payoff was the generation of a large body of scienlific information generatecl by a small number of researchers. Positive reactions of former has lecl to research at the farm level, focusing on the increases in maize yield due ro the benefits and the recluction in Striga bermonthica parasicism. A preliminary estimate of the impact can be ca lculatecl for Northern igeria w here gross revenue fro m soybean-maize rotation is 50 Lo 70% higher than continuous maize cropping. Severa! research and develo pment efforts are now underway testing soybean o r cowpea rotation with maize.